Perilaku Investasi di Indonesia: Kajian Jangka Pendek dan Jangka Panjang - Daru Wahyuni (Universitas Negeri Yogyakarta, 2004)
The purpose of this research was to know how domestic investment in Indonesia behaves both in the short term and in the long term. Data used were secondary data obtained from various sources. Those data would be analyzed by using a dynamic analysis tool consisted of a cointegration approach and an error correction model.Several findings obtained from this research were (1) ECT coefficient (4.16) significantly and statistically influenced domestic investment in Indonesia. It indicated that the error correction model used in this research was valid. (2) In the short term, national income variables and domestic interest rates did not significantly affect domestic investment while government investment variables and rate of exchange positively and significantly influenced domestic investment. Elasticity coefficient of the government investment and the exchange rate were 1.44 and 2.34 respectively. (3) By concerning time lag factor, the estimation results showed that the national incomes, the domestic interest rates, the government investment , and exchange rate of rupiah against US dollar in the previous 1 year significantly affected domestic investment. Their elasticity were 2.18, -1.18, -2.18 and 1.26 respectively. (4) In the long term, the national income variables and the exchange rate of rupiah against US dollar positively and significantly influenced domestic investment meanwhile the domestic interest rate variables and the government investment did not significantly influence domestic investment. The elasticity coefficient of the national income and exchange rate were 3.08 and 2.19 respectively.